An Exploration on EFL Teachers’ Perceptions Of effective 21st- Century Pedagogical Competencies - Renol Aprico Siregar; Endang Fauziati; Sri Marmanto (JEELS (Journal of English Education and Linguistics Studies), 2020)
The need for preparing highly qualified teachers with all the quintessential pedagogical competencies has been acknowledged as a preeminent priority in the educational world. This present study is intended to scrutinize the EFL teachersâ€™ perspectives and preferences in the 21st century pedagogical competence. The study was qualitatively conducted as a case study to retrieve a reputable understanding of the phenomenon. A semi-structured interview and a five-Likert scale questionnaire were used to collect the necessary data.Â The data of this study were taken from the purposively chosen informants regarding their familiarity and apprehension with the issue of this study. The results demonstrated that the teachers perceived the rapid development of technology and information as the key feature of the 21st-century learning, which is beneficial to furnish more comprehensive learning. Moreover, they predominantly conceived that the term 21st-century pedagogical competence focused on how teachers assimilate technology in the classroom and how to facilitate the studentsâ€™ creativity due to the widely opened sources of information which positively affect studentsâ€™ proficiency. It is suggested to consecutively provide more courses and training about confronting the 21st-century education to keep teachers voguish of any adjustments, innovations, and modifications in education.